Government Intervention of Harmful Products : A crosscultural explanation of public perceptions." - Agarwal, Nikunj (2012)
This dissertation report aims to answer the research question - "Public perception of government intervention in controlling the consumption of alcohol and tobacco in the UK and India". Due to tobacco consumption and misuse of alcohol the respective populations are facing significant social and economic costs. The manufacturers of these products have been blamed to an extent to aggravate the problem. The respective governments had to intervene to control the situation. The research will explore the public's perception on the efforts of the governments of India and UK which have been undertaken to control the consumption of tobacco and alcohol. It will look at the general perception of people on smoking and drinking alcohol also. The report will use primary data. It will be used to answer what the general public perceives of the government intervening in the consumption of alcohol and tobacco. Alongside it will also review the current literature available on the research question. The report will end with a summary to what was found out in relation to the research question. It will also list out the limitations of the research and suggestions for future research on the chosen research question. Finally the report will list the implications of the findings.